Accounting: A Smart Approach - Cathy Knowles; Mary Carey (Great Britain Oxford University Press, 2020)
Engaging and lively, clear and practical, this is the most applied accounting book written specifically for business and management students. Sam Smart is the budding entrepreneur on whom the case study at the heart of this book is based. Featured at the start of each chapter, we follow Sam as he goes from starting a small business, printing sports kits for local teams, to managing a global sports business. Throughout the course of the book he assesses the success of his business, finances activities, makes pricing decisions, opens new branches, looks at cash flow, and facilitates planning, control, and investment. As we follow the case study, the core topics central to accounting are covered with clarity, imagination, and relevance, giving students the support they need to complete their course and exams with confidence. The wealth of additional examples and self-test exercises available alongside the case study enable students not only to develop an appreciation of how accounting information allows a manager to make key business decisions, but also to acquire the skills necessary to enable them to converse with accountants, and challenge their assumptions and methodologies.
Keywords: Accounting; Business; Textbooks; (ACC1057-N) Business Finance